How Do Firing Costs Affect Worker Flows in a World with Adverse Selection? - Kugler, Adriana D.; Saint‐Paul, Gilles (Journal of Labor Economics, 2004)
This article provides theoretical and empirical analyses of a firing costs model with adverse selection. Our theory suggests that, as firing costs increase, firms increasingly prefer hiring employed workers, who are less likely to be lemons. Estimates of re‐employment probabilities from the National Longitudinal Survey of Youth support this prediction. Unjust‐dismissal provisions in U.S. states reduce the re‐employment probabilities of unemployed workers relative to employed workers. Consistent with a lemons story, the relative effects of unjust‐dismissal provisions on the unemployed are generally smaller for union workers and those who lost their previous jobs due to the end of a contract.